Contribution of O. I. Nerovetskyi to the development of railway and bridge construction - Mykhailenko, H. H. (History of science and technology, 2015)
The contribution of an outstanding civil engineer O. I. Nerovetskyi to railway and bridge construction has been analysed in the article. O. I. Nerovetskyi was fully engaged to the development of railway network of Ukraine, Russia, Bielorus and the Caucasus region. Olexandr Inokentiiovych Nerovetskyi was known as one of the prominent Ukrainian bridge engineers at the beginning of the twentieth century. Construction of the most complicated (from the engineering point of view) projects has been focused on in the article. The author emphasizes that the railway network of Ukraine has been built due to hard work and selfless labour of talented engineers such as O. I. Nerovetskyi.